2007
DOI: 10.1016/j.jpainsymman.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Prevalence in Patients with Incurable Cancer: A Systematic Review

Abstract: The suffering of patients with incurable cancer is determined to a large degree by the presence and intensity of the symptoms of their disease. Knowledge of symptom prevalence is important for clinical practice. The main aim of this study was to obtain a reliable estimation of symptom prevalence in patients with incurable cancer by performing a systematic review of studies assessing this topic. We included 44 studies (including 25,074 patients) on overall symptom prevalence (Group 1) and six studies (including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
592
7
52

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 839 publications
(677 citation statements)
references
References 50 publications
(31 reference statements)
26
592
7
52
Order By: Relevance
“…The total symptom prevalence patterns (including those symptoms prevalent on inpatient admission and those that developed or recurred during the inpatient stay) were similar to that of other audits conducted in supportive and palliative care [20]. A systematic review of symptom prevalence in the last weeks of life found that 5 symptoms, (fatigue, pain, lack of energy, weakness and anorexia) occurred in more than 50% of all people [21]. The findings are also consistent with the data on the reasons that referral to specialized supportive and palliative care services occurs [14].…”
Section: What Data Are Supported By the Current Study?supporting
confidence: 66%
“…The total symptom prevalence patterns (including those symptoms prevalent on inpatient admission and those that developed or recurred during the inpatient stay) were similar to that of other audits conducted in supportive and palliative care [20]. A systematic review of symptom prevalence in the last weeks of life found that 5 symptoms, (fatigue, pain, lack of energy, weakness and anorexia) occurred in more than 50% of all people [21]. The findings are also consistent with the data on the reasons that referral to specialized supportive and palliative care services occurs [14].…”
Section: What Data Are Supported By the Current Study?supporting
confidence: 66%
“…Symptoms such as nervousness, depressed mood, worrying, anxiety and irritability contribute to PD [17] and are quite common in patients with advanced cancer. Nervousness for example, is experienced by almost 50% of incurable cancer patients, according to a systematic review in 25,074 patients [18]. Other symptoms, such as depressed mood, worrying, anxiety and irritability are reported by 39, 36, 30 and 30% of patients, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients diagnosed with cancer will receive treatment, and patients undergoing treatment experience a multitude of symptoms, including fatigue, pain, difficulty breathing, nausea, appetite loss, and unintentional weight change (2)(3)(4)(5). These symptoms can negatively impact one's ability to complete treatment as well as one's quality of life during and after treatment (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%